Life during the COVID-19 pandemic. Transformations of human contacts and relationships - Karkowska, Marta (Research on social problems in (pre-)pandemic reality, 2023)
The article discusses issues related to the transformations of social life in Poland caused by the emergence and spread of the Covid-19 disease. It discusses, among other things, observed at the micro-social level the transformations of previously practiced ways of contacting other people; perception of contacts with strangers or those who do not belong to the household or close family; changes in activities carried out in the public space; as well as transformations of patterns of social behaviors. The key causes of these phenomena and the consequences observed after the first year of the pandemic were also identified. The theoretical framework of the conclusions are the concepts of social ties and social change. The empirical basis for the conclusions is provided by materials obtained from a qualitative study conducted in 2020 in connection with the outbreak of the Covid-19 pandemic in Poland.  The study focused on social attitudes and lifestyles in the context of climate change. A second research project was carried out in 2021, and the researchers returned to the same interviewees with updated research questions.